Plant and Trees Pathogens: Isolation, Characterization and Control Strategies (1.0) - Salah-Eddine Laasli; Essaid Ait Barka; Rachid Lahlali (Journal of Fungi, 2023)
Agricultural production is under constant threat from biotic and abiotic stresses [...]